Bone marrow sparing by intensity modulated proton beam therapy in postoperative irradiation of gynecologic malignancies - Wark, Antje; Gupta, Anil; Meixner, Eva; König, Laila; Hörner-Rieber, Juliane; Forster, Tobias; Uzun-Lang, Kristin; Ellerbrock, Malte; Herfarth, Klaus; Debus, Jürgen; Arians, Nathalie (Technology in cancer research & treatment, 2024)
Purpose: The aim of this matched-pair cohort study was to evaluate the potential of intensity-modulated proton therapy (IMPT) for sparring of the pelvic bone marrow and thus reduction of hematotoxicity compared to intensity-modulated photon radiotherapy (IMRT) in the setting of postoperative irradiation of gynaecological malignancies. Secondary endpoint was the assessment of predictive parameters for the occurrence of sacral insufficiency fractures (SIF) when applying IMPT. Materials and Methods: Two cohorts were analyzed consisting of 25 patients each. Patients were treated with IMPT compared with IMRT and had uterine cervical (n = 8) or endometrial cancer (n = 17). Dose prescription, patient age, and diagnosis were matched. Dosimetric parameters delivered to the whole pelvic skeleton and subsites (ilium, lumbosacral, sacral, and lower pelvis) and hematological toxicity were evaluated. MRI follow-up for evaluation of SIF was only available for the IMPT group. Results: In the IMPT group, integral dose to the pelvic skeleton was significantly lower (23.4GyRBE vs 34.3Gy; p < 0.001), the average V5Gy, V10Gy, and V20Gy were reduced by 40%, 41%, and 28%, respectively, compared to the IMRT group (p < 0.001). In particular, for subsites ilium and lower pelvis, the low dose volume was significantly lower. Hematotoxicity was significantly more common in the IMRT group (80% vs 32%; p = 0009), especially hematotoxicity ≥ CTCAE II (36% vs 8%; p = 0.037). No patient in the IMPT group experienced hematotoxicity > CTCAE II. In the IMPT cohort, 32% of patients experienced SIF. Overall SIF occurred more frequently with a total dose of 50.4 GyRBE (37.5%) compared to 45 GyRBE (22%). No significant predictive dose parameters regarding SIF could be detected aside from a trend regarding V50Gy to the lumbosacral subsite. Conclusion: Low-dose exposure to the pelvic skeleton and thus hematotoxicity can be significantly reduced by using IMPT compared to a matched photon cohort. Sacral insufficiency fracture rates appear similar to reported rates for IMRT in the literature.
Gesehen am 11.11.2024